2006
DOI: 10.1080/10556790600804424
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and gravitational radiation of graviatoms

Abstract: Graviatom existence conditions have been found. The graviatoms (quantum systems around mini-black-holes) satisfying these conditions contain the following charged particles: the electron, muon, tau lepton, wino, pion and kaon. Electric dipole and quadrupole and gravitational radiations are calculated for the graviatoms and compared with Hawking's mini-hole radiation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 5 publications
(4 reference statements)
3
18
0
Order By: Relevance
“…Furthermore, in the nonrelativistic regime Mµ ≪ l, we expect the frequencies to be approximated by (32). Our numerical results conform to both expectations.…”
Section: B Bound State Frequencies: Schwarzschild (A = 0)supporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, in the nonrelativistic regime Mµ ≪ l, we expect the frequencies to be approximated by (32). Our numerical results conform to both expectations.…”
Section: B Bound State Frequencies: Schwarzschild (A = 0)supporting
confidence: 85%
“…This is the hydrogenic Schrödinger equation, but with the fine-structure constant α EM = e 2 /4πǫ 0 c replaced by the gravitational coupling α G = GMµ/ c. Hence the non-relativistic wavefunctions are hydrogenic, and the energy levels are given by (32). University for the continued use of their computing facilities.…”
Section: Appendix A: Non-relativistic Frequency Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of interest to consider so-called the graviatom of the positronium type, which is a bound state of pairs of particles of dark matter, taking into account only the gravitational interaction. The definition of the graviatom was proposed M. L. Fil'chenkov in [8]. Such graviatoms were formed in the early universe at the birth of pairs and can be preserved until the present era.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in this case the DeWitt self-force always exceeds the nonconservative radiation damping force; the energy spectrum and intensity of the electric dipole radiation were calculated for the case of black hole with masses ranging from 10 −5 g to 10 14 g [13] (see also [15]). The conditions of existence of a gravitationally bound quantum system with a neutral black hole as a nucleus were formulated in [16,17] where it was called graviatom.…”
Section: Introductionmentioning
confidence: 99%